2006
DOI: 10.1557/proc-0912-c05-07
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Sheet Resistance Measurement on Ultra-Shallow Profiles

Abstract: The accurate and reliable characterization of the sheet resistance of ultra-shallow (USJ) profiles is a key issue in the development of future CMOS technologies. Typically, conventional means, such as in-line four point probe measurements, have a limited accuracy due to the substrate contribution resulting from too much probe penetration, especially in the presence of highly doped underlying layers (such as well/halo-profiles). In this work, a series of advanced Boron doped layers (132 nm down to 2 nm) have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 6 publications
1
25
0
Order By: Relevance
“…In practical experiments it is difficult to position the electrodes closer than Yo = 4 Jlm from the barrier because this is done optically. Thus, we choose this position for the measurement of 5 (2). For each~y, 500 independent simulations were performed for a 20 Jlm pitch four-point probe.…”
Section: Simulated Measurement Errormentioning
confidence: 99%
See 1 more Smart Citation
“…In practical experiments it is difficult to position the electrodes closer than Yo = 4 Jlm from the barrier because this is done optically. Thus, we choose this position for the measurement of 5 (2). For each~y, 500 independent simulations were performed for a 20 Jlm pitch four-point probe.…”
Section: Simulated Measurement Errormentioning
confidence: 99%
“…Prior experimental work has revealed the need for characterization techniques like the micro four-point probe (M4PP) to accurately characterize sheet resistance of ultra shallow junctions (USJ) [2] with high spatial resolution [3]. Recently, we demonstrated the ability to perform reproducible micro Hall effect measurements to characterize sheet carrier 978-1-4244-1951-7/08/$25.00 ©2008 IEEE density and mobility of shallow implants in both Si and Ge using M4PP [4].…”
Section: Introductionmentioning
confidence: 99%
“…Resistance measurements using micro four-point probes (M4PP) [4] is a well-established technique used to monitor the sheet resistance of semiconductor surfaces [5,6,7]. Within the last decade the use of M4PP metrology has broadened from development and process monitoring for tunnelling spin valves [8] to characterization of shallow semiconductor junctions [9].…”
Section: Introductionmentioning
confidence: 99%
“…Four-point probes are widely used for sheet resistance characterization since essentially no additional sample preparation is necessary. 1 It has recently been shown that micro-four-point probes 3 are able to accurately measure sheet resistance of ultrashallow junctions with high spatial resolution 4 and without artifacts due to probe penetration 5 and leakage current; 6 moreover carrier profiling on beveled ultrashallow junctions has been demonstrated. 7,8 The implantation and annealing processes used in semiconductor fabrication today cannot guarantee 100% activation of the implanted dose, and defects not removed by annealing may lead to reduced carrier mobility.…”
Section: Introductionmentioning
confidence: 99%